Human differentiated eosinophils release IL-13 in response to IL-33 stimulation - Uchida, Amiko M.; Ro, Gabrielle; Qiang, Li; Peterson, Kathryn A.; Round, June; Dougan, Michael; Dougan, Stephanie K. (Frontiers in Immunology, 2022)
Objective: Eosinophils are hallmarks in allergic type 2 inflammation and are known to release cytotoxic granule proteins that contribute to inflammation. Eosinophils develop in the bone marrow from hematopoietic stem cells and once mature, have a limited lifespan in culture, making them difficult to study ex vivo. IL-33 has increasingly been shown as a key regulator of type 2 inflammation via signaling through its receptor, ST2. The present study was conducted to detail a method of eosinophil differentiation from hematopoietic stem cells and determine the response to IL-33. Methods: CD34+ and CD14+ cells were isolated from donor apheresis cones and differentiated into eosinophils or macrophage controls, respectively. Morphologic, transcriptional and protein analyses were performed to validate this method of eosinophil differentiation. The effect of IL-33 on differentiated eosinophils was assessed using qPCR, immunofluorescence, and multiplex cytokine array. Results: CD34 differentiated eosinophils appear morphologically similar by H&E and express eosinophil peroxidase (EPX) protein as well as the conventional eosinophil transcripts EPX, CLC, and MBP. In addition, differentiated eosinophils expressed both isoforms of the IL-33 receptor, ST2L and sST2 throughout the differentiation process. Transcript levels of both IL-33 receptors were up-regulated by treatment with IL-33 at earlier timepoints in the differentiation. These cells also expressed IL-4 and IL-13 mRNA which were up-regulated by IL-33 as well. Notably, IL-13 expression was significantly higher with IL-33 treatment compared to media control at every timepoint measured. IL-33 significantly increased cellular secretion of IL-13 protein at most timepoints throughout differentiation. IL-8, LIF, CCL1, CCL5, CCL7, and CCL8 were also significantly secreted after IL-33 stimulation. Conclusions: Our findings suggest that CD34 differentiated eosinophils are morphologically and phenotypically similar to peripheral eosinophils. The release of specific cytokines in direct response to IL-33 may contribute to the pathogenesis of type 2 inflammation and facilitates new avenues for studying eosinophils as effector cells in vitro.